مستوى فهم قضايا الثقافة العلمية المرتبطة بالعلم والتكنولوجيا والمجتمع لدى طلبة كلية الآداب والعلوم الإنسانية - الشياب، معن بن قاسم (مكتب التربية العربي لدول الخليج, 2016)
The study aims to monitor the level of understanding of scientific culture is¬sues related to science, technology and society among the students of Arts and Humanities. The total number of students in the study is 858 from the College of Arts & Humanities in Yanbu. Taibah University white the sample of the study consists of 127 students randomly selected in the second semester of the aca-demic year 1436/1437. The researcher developed a test of 50 multi-choice questions to measure the understanding of scientific culture issues related to science, technology and so-ciety. After the validation, the test was applied on the sample of the study, then the data was collected and statistically analyzed with SPSS application. The results showed that: • The arithmetic average of students’ performance level in understanding scientific culture issues related to science, technology and society was (24 82) which did not reach the level of precision of 70% • No statistically differences were detected at (0.05 a) in the level of students understanding due to study variables (gender, academic level, academic specialization). In the light of the results, the researcher recommends that the academic preparation programs are to adopt objectives within their courses to qualify the students in the concept of the scientific culture and related issues.
هدفت الدراسة تقصي مستوى فهم قضايا الثقافة العلمية المرتبطة بالعلم والتكنولوجيا والمجتمع لدى طلبة كلية الآداب والعلوم الإنسانية، تكون مجتمع الدراسة من (858) طالبًا وطالبة، في كلية الآداب والعلوم الإنسانية بينبع بجامعة طيبة، فيما تكونت عينة الدراسة من (127) طالبًا وطالبةً تم اختيارهم بالطريقة العشوائية البسيطة، خلال الفصل الدراسي الثاني من العام الجامعي 1436/1437هـ. تم تصميم اختبار لقياس فهم قضايا الثقافة العلمية المرتبطة بالعلم والتكنولوجيا والمجتمع، تكون من (50) فقرة من نوع الاختيار من متعدد، وبعد التأكد من صدقه وثباته، طبق على أفراد عينة الدراسة، ثم جمعت البيانات وحللت إحصائيًّا باستخدام برنامج SPSS. وقد أسفرت الدراسة عن النتائج التالية: بلغت قيمة المتوسط الحسابي لمستوى أداء الطلبة على اختبار فهم قضايا الثقافة العلمية المرتبطة بالعلم والتكنولوجيا والمجتمع (24.82)، وهي قيمة أقل من العلامة المحكية (35) وبفارق ذي دلالة إحصائية عند مستوى الدلالة (0.05 =a). عدم وجود أثر ذي دلالة إحصائية عند مستوى الدلالة (0.05 =a) يعزى لمتغيرات الدراسة (النوع الاجتماعي، المستوى الدراسي، التخصص الأكاديمي). في ضوء نتائج الدراسة، تمت التوصية بعدة توصيات منها: تبني برامج الإعداد الأكاديمي أهدافًا وموضوعات ضمن مقرراتها بصورة صريحة وهادفة لتأهيل الطلبة في مفهوم الثقافة العلمية وما يرتبط بها من قضايا مرتبطة بالعلم والتكنولوجيا والمجتمع.
Keywords: التعليم الجامعي; طلبة الجامعة; العلم التكنولوجي; الثقافة العلمية